Advanced Training on Climate Data Tools (CDT) and AWS Data Tools (ADT): Installation and Training for the Ethiopian National Meteorological Agency (NMA) - Faniriantsoa, Rija; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The International Research Institute for Climate and Society (IRI) conducted an advanced training on Climate Data Tool (CDT), as well as installed the new Automatic Weather Station Data Tool (ADT) and conducted training on this tool with staff from the NMA’s head office. This ADT installation and training was requested by the NMA’s Meteorological Data and Climatology Directorate (MDCD), as there have been challenges in Ethiopia and generally in Africa in accessing and processing automatic weather station (AWS) data collected by different systems/networks (Vaisala, Edkon, KOICA, etc.) which are on different servers and in different formats. The web-based ADT tool was created to help with this, including quality control, processing and visualization of merged AWS data.